Evaluation of Students' Mastery of Semantic Entailment as Reflected in Their Descriptive Text Writing - Rika Setyawati; Januarius Mujiyanto; Zulfa Sakhiyya (English Education Journal, 2023)
Some challenges in teaching writing are making students interpret, analyze, and build reasoning for a coherent text. To address this issue, such research is included in a branch of linguistics, namely semantics. This research evaluates the students’ mastery of semantic entailment as reflected in their descriptive text writing. The research method applied was a descriptive qualitative design. The data was taken from the 30 explanatory texts written by the eighth-graders of MTs Ar Ridlo Pekuncen 2022/2023. The technique of collecting data was document text. The method of data analysis was triangulation. The results revealed that the evaluation of students’ mastery of one-way entailment is 90%; there were 27 of 30 students. Almost all of the students (generally) are very masterful. Next, the evaluation of students’ mastery of two-way entailment is 36.67% (N=11). Furthermore, only 30.00% of the students (N=9) can master negative entailment. The least (a fraction) mastered was metaphorical entailment, 13.33% (N=4). The easiest for students to master was the one-way entailment. In contrast, the metaphorical entailment was the most difficult. Thus, it can be safely said that the students have difficulty imagining the object in their sentences. For that reason, future research may investigate the factors that cause problems in metaphorical entailment among students.